Online News Articles Alleged Extortion Case Firli Bahuri Kompas.Com Critical Discourse Analysis Study Model Teun A. Van Dijk - Susilawati, Dewi; Sakrim, Sakrim (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study is a critical discourse analysis of online news articles related to the alleged extortion case committed by Firli Bahuri in the online media Kompas.com. This discourse analysis uses the theory of Teun A. Van Dijk focusing on text analysis with three problem focuses, namely, macrostructure, superstructure, and microstructure. The purpose of this study is to describe the data found in Kompas.com online news articles related to the Firli Bahuri extortion case according to the three problem focuses that have been mentioned. The data sources found in this study were taken from news articles from September to December 2024 editions. The type of research conducted is qualitative. In this study, the approach chosen from the qualitative research method is a descriptive approach, namely a research method by describing the results of the data that has been obtained.